2004
DOI: 10.1021/bi0481491
|View full text |Cite
|
Sign up to set email alerts
|

pKa and Aggregation of Bilirubin:  Titrimetric and Ultracentrifugation Studies on Water-Soluble Pegylated Conjugates of Bilirubin and Fatty Acids

Abstract: A water-soluble conjugate (1) with intact carboxyl groups was prepared by addition of poly(ethylene glycol) thiol (MPEG-SH) regiospecifically to the exo vinyl group of bilirubin. (1)H and (13)C NMR and absorbance spectroscopy in CDCl(3) and DMSO-d(6) confirmed the assigned structure and showed that pegylation did not disrupt the hydrogen-bonded ridge-tile conformation of the pigment moiety. Aqueous solutions of 1 were optically clear, but NMR signals were seen only from the MPEG portion and none from the tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 76 publications
2
62
1
Order By: Relevance
“…As a negative control, the red fluorescence disappeared when the bilirubins were dissolved in DMSO ( Figure 3A, red curve), in which the bilirubins were monomeric. 59 These evidence support that the bilirubin red fluorescence originates from its dimers. Although the single-photon fluorescence of bilirubin dimers was weak at pH 7.4 ( Figure 3A, black curve), the intensity was enhanced 3 times after association with HSA ( Figure 3B).…”
Section: Analytical Chemistrymentioning
confidence: 63%
“…As a negative control, the red fluorescence disappeared when the bilirubins were dissolved in DMSO ( Figure 3A, red curve), in which the bilirubins were monomeric. 59 These evidence support that the bilirubin red fluorescence originates from its dimers. Although the single-photon fluorescence of bilirubin dimers was weak at pH 7.4 ( Figure 3A, black curve), the intensity was enhanced 3 times after association with HSA ( Figure 3B).…”
Section: Analytical Chemistrymentioning
confidence: 63%
“…[16] had reported the formation of UCB aggregates in some CHCl 3 solutions when pure distilled CHCl 3 , exposed to Parafilm ® or plastic caps, was used as solvent. They suggested that "adventitious lipid contaminants can cause aggregation in CHCl 3 " and that this may be relevant to our CHCl 3 -water partition studies [3].…”
Section: Discussionmentioning
confidence: 99%
“…43,46 The presence and persistence of folded, intramolecularly hydrogen-bonded conformation of bilirubin and its anions in solution is also experimentally supported by studies of Lightner and Nogales. 46 The hydrogen-carbon distances 11,47 account for the hydrogen bond effect (proton deshielding and a further downfield shift for these proton resonances) of the internal UCB hydrogen bond network.…”
Section: E Explicit Solvation (Partially Ab Initio and Fully Semiempmentioning
confidence: 99%